Reporting of concussion-like symptoms after cycling crashes: A survey of competitive and recreational cyclists - Rice, S.; Iaccarino, M. A.; Bhatnagar, S.; Robidoux, G.; Zafonte, R.; Kotler, D. H. (Journal of Athletic Training, 2020)
Context: Cycling crashes are common among recreational and competitive riders and may result in head and bodily trauma. Information is limited regarding the signs and symptoms of head injury (HI) after cycling crashes, medical treatment, and recovery.